REPORT OF THE 12TH INTERNATIONAL SCIENTIFIC CONFERENCE "TRANSFORMATIONAL PROCESSES IN SPORT - SPORTS ACHIEVEMENTS" - Selçuk Akpinar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The article discusses the highlights of the 12th International Scientific Conference on Transformation Processes in Sport "Sports Performance", which was held in Podgorica, Montenegro. The event comprised oral and poster sessions. Professor, Duško Bjelica, President of Montenegrin Sports Academy, gave one of the opening speeches.